Cervical Cancer Screening Uptake and Experiences of Black African Immigrant Women in Canada - Abosede C. Ojerinde; Sally E. Thorne; A. Fuchsia Howard; Arminee Kazanjian (SAGE Publishing, 2024)
Cervical cancer is one of the leading causes of cancer-related death among African women. Unfortunately, in most sub-Saharan African nations, women are vulnerable if they are unaware that cervical cancer is preventable with frequent screening and early treatment. The aim of this study was to examine Black African immigrant women's perceptions and experiences of cervical screening in British Columbia, Canada. Twenty Black African immigrant women were interviewed using the qualitative research method Interpretive Description. Data collection approaches included indepth interviews and analytic memos. Data were analyzed using a constant comparative technique guided by a socioecologic framework to capture subjective experiences and perceptions. Four key themes were identified, including confusing conceptualizations about cancer and cancer screening, competing priorities, concerns for modesty, and commitment to culture. The study findings point to the need for more active approaches to promoting cervical screening for this population.